KEBIJAKAN INDONESIA TERHADAP PERUSAHAAN MULTINASIONAL (STUDI KASUS IMPLEMENTASI PROGRAM TANGGUNG JAWAB SOSIAL PERUSAHAAN DI KABUPATEN SIAK TAHUN 2013-2016) - Velatio, Nugraha; ", Afrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research describes the policy of Indonesia toward implementations of corporate social responsibility (study case in implementations of corporate social responsibility in Siak Regency in 2013-2016). Nowdays the developing states in Indonesia not only have done by government. The corporations that have invested in Indonesia basen on regulation number 40 years of 2007 about coroprations that severy corporate have done a corporate social responsibility especially Siak Regency.The research method used was a qualitative with descriptive as a technic of the research. Writer collects data from books, encyclopedia, journal, mass media and websites to analyze the policy of Indonesia toward implementations of corporate social responsibility (study case in implementations of corporate social responsibility in Siak Regency in 2013-2016). The theories applied in this research are neo realism perspective with the foreign policy theory by William D Coplin and corporate social responsibility concept.The research shows that the policy of Indonesia toward implementations of corporate social responsibility (study case in implementations of corporate social responsibility in Siak Regency in 2013-2016) are have done by some steps are Indonesia government have done a regulations about implementations of corporate social responsibility are regulations number 40 years of 2007 about corporate social responsibility and for Siak Regency have a local regulations number 6 years of 2011 about corporate social responsibility, government of Siak Regency create a forum of CSR and implemented corporate social responsibility in helath, educations, environment and social empowerment program.Key words: policy, corporate social responsibility and Siak.